Reconfiguraç\~oes da aç\~ao estatal na política de infraestrutura no período recente: Avanços e limites - Raphael Amorim Machado; Alexandre de Ávila Gomide; Roberto Rocha Coelho Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The objective of this text is to present an overview of the trajectory of the infrastructure policies in Brazil in the recent period (2005-2013). In order to do so, it highlights the main efforts and advances towards the resumption of the role of the federal government in the sector, as well as it points to the limits and obstacles that contributed to the production of incomplete results and partial achievements in terms of project implementation and effectiveness. The analysis of the historical trajectory draws from three interrelated analytical categories: political-institutional environment, institutional arrangements and instruments of public action. The main conclusion is that the advances in the development of instruments and arrangements were incomplete and insufficient. Incomplete because they failed to overcome some of internal limitations (such as planning failures and decision-making processes isolated from civil society). Insufficient because, even if they were fully developed, they would still face difficulties in counterbalancing external constraints and the governance challenges imposed by the Brazilian political-institutional environment (such as a fragmentation of the state apparatus and the short-term interests of political actors inside the logic of the political system).
Keywords: H54; O18; O21; 330; infrastructure; instruments; public policy arrangements; investment